La construction de la loi du 5 mars 2007. Pour une analyse sociopolitique des mutations de la Protection de l’enfance - Fadila Chourfi (Sociétés et Jeunesses en Difficulté)
The reform of child protection as a result of the law of 5 March 2007 comes in the wake of strong doubts over the effectiveness and efficiency of its provisions. The emergence of new forms of social vulnerability would render it ineffective. The media coverage of cases of abuse and rape of children by adults, the Angers and Outreau Affairs will contribute to putting child protection reforms firmly on the agenda.  The construction of the law rests on the assertion of reflections developed and shared by those involved in child protection.  The pragmatic approach will thereby be emphasised by several commentators.  In our view, “the law and the way in which the law is produced reflect the reorganisation of the public prosecution system2”. This approach serves to emphasise, beyond the apparent consensus, a reorganisation of the scope of child protection around prevention and the strengthening of regional territory as the “spearhead” of the provisions, while tensions subsist over the target group for child protection and the role of the State.